“Seeing in the dark”: the aesthetics of disappearance and remembrance in the work of Alberto Rey - Lewthwaite, Stephanie (Cambridge University Press, 2017)
This article examines how contemporary Cuban American artists have experimented with visual languages of trauma to construct an intergenerational memory about the losses of exile and migration. It considers the work of artist Alberto Rey, and his layering of individual loss onto other, traumatic episodes in the history of the Cuban diaspora. In the series Las Balsas (The Rafts, 1995-99), Rey explores the impact of the balsero (rafter) crisis of 1994 by transforming objects left behind by Cuban rafters on their sometimes ill-fated journeys to the United States into commemorative relics. By playing on a memory of absence and the misplacement of objects found along the migration route of the Florida Straits, Rey’s visual language transmits the memory of grief across time, space and generational divides. Rey’s visual strategies are part of an “extended memory” tied to the aesthetics of disappearance and remembrance in contemporary Cuban American art. His use of objects as powerful memory texts that serve to bring fragmented autobiographical, family, and intergenerational testimonies of loss together, suggests how visual artists can provide us with more collective, participatory and redemptive models of memory work.